In Vitro Rooting Improvement of Adult Pistachio, Pistacia vera L. 'Atli' - Tilkat, E.; Onay, A.; Tokatli, Y. Ozden (Int Soc Horticultural Science, 2009)
Axenic cultures of Pistacia vera L. 'Atli' initiated on agar solidified Murashige and Skoog (MS) medium with Gamborg vitamins supplemented with different concentrations of 6-benzyladenine (BA) and indole-3-acetic-acid (IAA) were proliferated and maintained on an MS medium supplemented with 4.4 mu M BA. Using these proliferated cultures, effects of: i) washing of the basal-cut-ends in sterile distilled water; ii) dipping of the basal-cut-ends in the different indole butyric acid (IBA) solutions; iii) cloned shoots; and iv) explant sizes (1.0, 2.0, 3.0 and 4.0 cm long) were assessed for root induction. The highest rooting frequency (92%) of microshoots was recorded at 4.0 cm long cloned and twice washed microshoots. Rooting was apparent within 14 days. The present study also aimed to reduce the occurrence of basal callus production. The microshoots cultured from the cloned shoots produced less calli than the mixed population, and developed roots that resemble the seedling plantlets. Those plantlets that had been rooted and exposed to sterile compost were able to acclimatize readily. Major improvement of the present study over previously published protocols has been achieved with the improvement of the in vitro rooting percentages of adult pistachio plantlets.
1st International Symposium on Biotechnology of Fruit Species - BIOTECHFRUIT -- JUL 14, 2009 -- Dresden, GERMANY
Keywords: acclimatization; callus; IBA; mature male tree; micropropagation